PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS DI KLINIK ALISAH TREISYA KECAMATAN MEDAN AREA TAHUN 2022 - Eka Sriwahyuni; Intan Suwati Marpaung (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Breast milk is the main food for babies. It is very important to pay attention to postpartum mothers in providing breast milk to their babies by consuming foods that can increase milk production. Banana flower contains laktogogum which can stimulate oxytocin and prolactin hormones such as alkaloids, polyphenols, steroids, flavonoids, which are effective in increasing breast milk production. The purpose of this study was to determine the effect of banana heart consumption on increasing breast milk production in postpartum mothers at the Alisah Treisya Clinic, Medan Area in 2022. This type of research was a quasi-experimental with a one-group pretest-posttest design. By using the purposive sampling technique, the sample in this study were 10 postpartum mothers whose milk production was not smooth. Wilcoxon statistical test data processing. The results showed that the production of postpartum mother's milk before being given a banana heart was not smooth and the production of postpartum mother's milk after being given a banana heart increased by 9 respondents (90.0%). Wilcoxon statistical test shows that the significant value of p-value = 0.003 < (0.05), so Ha is accepted. The conclusion of the study, which means that there is an effect of banana heart consumption on increasing breast milk production for postpartum mothers at the Alisah Treisya Clinic, Medan Area District in 2022.